On History of Construction of Oil Refineries Supplied to the USSR under Lend-Lease (1941—1945) - E. V. Bodrova; V. V. Kalinov (Научный диалог, 2020)
On the basis of archival materials, the issue of the construction of oil refineries set up in the USSR under lend-lease in accordance with the agreement signed with the United States in 1942 is examined, which is very relevant in the context of heightened discussions about the problems related to the history of World War II. The novelty of the research is determined not only by the introduction of new archival documents into scientific circulation, but also by an attempt to determine more precisely the reasons for the failure of the planned dates of commissioning of oil refineries. The results of the analysis of reports by American specialists are presented, which allowed to objectively consider the problems that arose during construction. Special attention is paid to the attempts of the authors of these documents to determine the main reasons for the construction slowdown. The changes in the attitude of Americans to construction managers, the management system during 1944 are commented. It is shown that their dissatisfaction with the position of consultants was expressed in the reports. It is concluded that our own production of fuel for the active army in our country was constantly growing and largely provided the front. It is proved that the commissioning of oil refineries supplied by the United States after the end of the war could not influence its outcome, but later became the basis for the creation of the refining industry in the lower Volga region.